2015
DOI: 10.1902/jop.2015.150123
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Phospholipase D in Periodontitis and Its Role in the Inflammatory and Osteoclastic Response by Nicotine‐ and Lipopolysaccharide‐Stimulated Human Periodontal Ligament Cells

Abstract: To the best of the authors' knowledge, this study is the first to demonstrate that PLD isoform inhibition has anti-inflammatory and antiosteoclastogenic effects and thus may be a therapeutic target for the treatment of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
(148 reference statements)
1
3
0
Order By: Relevance
“…Here, we demonstrate that HG exposure increases PLD1 and PLD2 mRNA levels in ARPE-19 cells. In agreement with our results, the inhibition or silencing of either PLD1 or PLD2 has been shown to inhibit nicotine- and LPS-induced ERK1/2 and NFκB activation, COX-2 expression, and secretion of tumor necrosis factor α, IL-1 β, and IL-8 in human periodontal ligament cells [ 36 ]. In addition, it has been reported that a high glucose environment induces and increases PLD1 expression in pancreatic beta cells [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Here, we demonstrate that HG exposure increases PLD1 and PLD2 mRNA levels in ARPE-19 cells. In agreement with our results, the inhibition or silencing of either PLD1 or PLD2 has been shown to inhibit nicotine- and LPS-induced ERK1/2 and NFκB activation, COX-2 expression, and secretion of tumor necrosis factor α, IL-1 β, and IL-8 in human periodontal ligament cells [ 36 ]. In addition, it has been reported that a high glucose environment induces and increases PLD1 expression in pancreatic beta cells [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Here resistin showed the regulation of these factors and exerted antiinflammatory effects on this chronic periodontal disease cell model (78). Nicotine plus LPS likewise upregulated iNOS, COX-2, NO, PGE2, TNF-a, IL-1b, IL-8, some TRAP (+) cells, and resorption via PI3K/PKC/Akt/MAPK (P38, JNK, ERK) and the NF-kB/c-Fos/NFATc1 signaling axis, involved in inflammatory bone destruction and osteoclast differentiation, with an increase in phospholipase D (PLD) 1 and PLD2 isoforms (79). When human periodontal ligament cells were cocultured with CD4 + T cells, nicotine (10 -5 M, 24 h) dramatically repressed cell viability and increased apoptosis, which was associated with the collapse of periodontal tissues and elevated matrix metalloproteinases MMP1, MMP3, and cytokines IL-1b, IL-6, IL-17, IL-21, and chemokines CXCL12.…”
Section: Pro-inflammatory Effect Of Nicotine On Oral Diseasesmentioning
confidence: 99%
“…Periodontal disease is characterized by an inflammatory reaction of periodontal tissue that leads to the progressive destruction of tooth-associated structures including alveolar bone, periodontal ligament (PDL) and cementum [ 2 ]. PDL cells (PDLCs) located between the tooth cementum and bone play a major role in alveolar bone metabolism in periodontal health and disease because of their ability to secrete factors that regulate the homeostasis of connective and osseous tissue, including inflammatory cytokines and major osteoblast or osteoclast regulators [ 3 , 4 , 5 , 6 ]. Cementoblasts are responsible for the production of cementum, which is the gold standard in periodontal regeneration [ 7 ].…”
Section: Introductionmentioning
confidence: 99%